Optimization of Lip balm Formulation Containing Beetroot Extract (Beta Vulgaris L.) With a Combination of Grapeseed oil and Avocado oil Using the Simplex Lattice Design Method - ananda, ardini; Rosanti, Afi Sania; Dwiningrum, Riza; Suswidiantoro, Vicko (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Lip balm, as a semi-solid preparation, can be used to moisturize and protect the lips from dryness and chapping. The use of natural colorants and emollients derived from natural sources is considered safer and more environmentally friendly. Beetroot (Beta vulgaris L.) contains betacyanin as a natural pigment, while grapeseed oil and avocado oil provide emollient properties that help moisturize and nourish the lips. This study aimed to optimize the lip balm formulation containing beetroot extract, grapeseed oil, and avocado oil using Design Expert software version 13 through the Simplex Lattice Design (SLD) method. Ten formulations were produced and evaluated for pH, spreadability, and adhesiveness. The results showed that variations in composition affected the physical characteristics of the lip balm. Grapeseed oil improved spreadability, while avocado oil influenced pH and enhanced adhesiveness. The combination of the three ingredients exhibited synergistic and antagonistic interactions on the physical properties depending on the proportion of each component. The optimum formula was obtained in formulation 5, with a composition of 10% beetroot extract, 10% avocado oil, and 5% grapeseed oil, yielding a desirability value of 1.000. Validation results showed good agreement between predicted and experimental data. Statistical validation using the Wilcoxon test and one-sample t-test indicated p-values > 0.05,suggesting no significant differences. Thus, the model was validated and considered reliable for predicting formulation outcomes. This study successfully optimized a natural lip balm formulation with desirable physical properties, highlighting the potential of beetroot extract as asafe natural colorant in combination with emollient oils.